SHEAR STRESSES OF HOLLOW CYLINDRICAL CONCRETE BEAMS MADE WITH RECYCLED CERAMICS AGGREGATES - Salman Chiad Alharishawi, Salam (Journal of Applied Engineering Science, 2026)
The main focus of the study presented in the work is an experimental investigation into the effects related to recycled ceramic coarse aggregates from the industrial brick waste on reinforced concrete beams (RCBs) shear behavior. For such an aim, a total of twelve concrete beams with 250mm height, 1200mm length, and 140mm width have been employed. A total of six Normal Concrete Beams (NCB) models made up of three Solid Normal Concrete Beams (SNCB) and Hollow Normal Concrete Beams (HNCB). Of the six models of Recycled Ceramic Concrete Beams (RCCB), there are also three Solid Recycled Ceramic Concrete Beams (SRCCB) and three Hollow Recycled Ceramic Concrete Beams (HRCCB). At such percentages of 0% and 30%, the weight related to coarse aggregate in concrete mixes is replaced with crushed ceramic that is acquired from building demolition wastes. A total of four points on the samples were examined for bending. The mid-span of the beam had the most deflection. The test evaluated the behavior related to beam concrete with the waste material by measuring the ultimate shear strength and diagonal cracking load. The experiment was designed to determine the impact of crushed ceramic on mechanical characteristics of RCBs. Additionally, the results show that, when compared to control samples, adding crushed ceramic improved the properties of the samples in shear behavior with reference to crushed ceramic concrete beams. Results have shown that the use of recycled ceramic aggregates caused a reduction in ultimate shear capacity of approximately 10–15% compared with conventional beams, while reducing stirrup spacing significantly enhanced shear resistance and crack control. Results have confirmed that recycled ceramic aggregates can be effectively used in reinforced concrete beams without significantly compromising structural performance. This study is limited to a 30% replacement ratio and monotonic static loading conditions. To the best of the authors’ knowledge, limited studies investigated combined effect of recycled ceramic aggregates and longitudinal hollow sections on shear behavior of reinforced concrete beams. This study provides additional information about the feasibility of utilizing ceramic waste in structural applications, thereby supporting sustainable construction practices and reducing environmental impacts associated with construction waste.
Keywords: shear behavior; recycled ceramic aggregates; hollow concrete beams; reinforced concrete beams; sustainable concrete; crack patterns; load–deflection behavior